2006
DOI: 10.1021/nl060771m
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes as Electrodes for Dielectrophoresis of DNA

Abstract: .Dielectrophoresis can potentially be used as an efficient trapping tool in the fabrication of molecular devices. For nanoscale objects, however, the Brownian motion poses a challenge. We show that the use of carbon nanotube electrodes makes it possible to apply relatively low trapping voltages and still achieve high enough field gradients for trapping nanoscale objects, e.g., single molecules. We compare the efficiency and other characteristics of dielectrophoresis between carbon nanotube electrodes and litho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 24 publications
3
69
0
Order By: Relevance
“…As suggested by Brody and co-workers [26], carbon nanotubes (CNT) present a natural candidate for DEP nanoelectode due to their small diameter ($1 nm in the case of single-walled carbon nanotube and a few nanometers in the case of multiwalled carbon nanotube). Several groups reported application of CNTs as electrodes for DEP trapping [27][28][29][30][31]. Nanoscale gaps in CNTs can be created by several methods such as FIB lithography [29,30], electrical breakdown [31] or oxidative plasma ablation [32].…”
Section: Fabrication Of Dielectrophoretic Traps and Choice Of Dep Parmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested by Brody and co-workers [26], carbon nanotubes (CNT) present a natural candidate for DEP nanoelectode due to their small diameter ($1 nm in the case of single-walled carbon nanotube and a few nanometers in the case of multiwalled carbon nanotube). Several groups reported application of CNTs as electrodes for DEP trapping [27][28][29][30][31]. Nanoscale gaps in CNTs can be created by several methods such as FIB lithography [29,30], electrical breakdown [31] or oxidative plasma ablation [32].…”
Section: Fabrication Of Dielectrophoretic Traps and Choice Of Dep Parmentioning
confidence: 99%
“…Törmä and co-workers used DEP to assemble 140 nm long DNA molecules between 100 nm spaced electrodes for electrical characterization of DNA [50]. The same group used DNA molecules to test the efficiency of carbon nanotube as an electrode for DEP [28]. In addition, the group studied the polarizability of DNA molecules and its dependence on DEP frequency and DNA length [36].…”
Section: Dielectrophoretic Manipulation Of Biomaterials and Small Orgmentioning
confidence: 99%
“…Due to the field non-uniformity, stretched DNA dielectrophoretically moves towards the electrode edge until one end comes into contact. On the basis of this behaviour many researchers have used AC electrokinetics to manipulate DNA (Walti et al, 2007;Lapizco-Encinas & Palomares, 2007;Washizu et al, 1995Washizu et al, & 2004Dewarrat et al, 2002;Asbury et al, 2002;Washizu, 2005;Tuukkanen et al, 2006;Chou et al, 2002;Kawabata & Washizu, 2001;Yamamoto et al, 2000;Wang et al, 2005). For example, a modified interdigitated microelectrode array, termed "zipper electrode" by the authors, has been reported to concentrate a wide range of nanoparticles of biological interest, such as the influenza virus and DNA (Hübner et al, 2007).…”
Section: Dnamentioning
confidence: 99%
“…One important application of CNT forming the high electric field is an electron emission source for the flat panel display device (Bonard et al 2002). CNT is also applicable as a ''nanoelectrode'' generating higher intensity electrical field gradients, which can produce high DEP force without the need for large electrode potentials (Tuukkanen et al 2006). When CNTs are trapped and attached to a microelectrode under positive DEP force as illustrated in Fig.…”
Section: Basic Proceduresmentioning
confidence: 99%